The clinical efficacy of type 2 monoclonal antibodies in eosinophil-associated chronic airway diseases: a meta-analysis - Wu, Yuan; Huang, Mengfen; Zhong, Jinyao; Lu, Yue; Gan, Kao; Yang, Rongyuan; Liu, Yuntao; Li, Jiqiang; Chen, Jiankun (Frontiers in Immunology, 2023)
Background Anti-type 2 inflammation therapy has been proposed as a treatment strategy for eosinophil-associated chronic airway disorders that could reduce exacerbations and improve lung function. We performed a meta-analysis of randomized controlled trials to assess the effectiveness of type 2 monoclonal antibodies (anti-T2s) for eosinophil-associated chronic airway disorders. Methods PubMed, Embase, Web of Science, and Cochrane Library were searched from their inception to 21 August 2022. Randomized clinical trials evaluating the effectiveness of anti-T2s versus placebo in the treatment of chronic airway diseases were selected. The outcomes were exacerbation rate and change in pre-bronchodilator forced expiratory volume in 1 s (FEV1) from baseline. The Cochrane Risk of Bias Assessment Tool 1.0 was used to evaluate the risk of bias, and the random-effects or fixed-effect model were used to pool the data. Results Thirty-eight articles concerning forty-one randomized clinical trials with 17,115 patients were included. Compared with placebo, anti-T2s therapy yielded a significant reduction in exacerbation rate in COPD and asthma (Rate Ratio (RR)=0.89, 95%CI, 0.83-0.95, I2 = 29.4%; RR= 0.59, 95%CI, 0.52-0.68, I2 = 83.9%, respectively) and improvement in FEV1 in asthma (Standard Mean Difference (SMD)=0.09, 95%CI, 0.08-0.11, I2 = 42.6%). Anti-T2s therapy had no effect on FEV1 improvement in COPD (SMD=0.05, 95%CI, -0.01-0.10, I2 = 69.8%). Conclusion Despite inconsistent findings across trials, anti-T2s had a positive overall impact on patients’ exacerbation rate in asthma and COPD and FEV1 in asthma. Anti-T2s may be effective in treating chronic airway illnesses related to eosinophils. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022362280.